A case of electromagnetic interference between HeartMate 3 LVAD and implantable cardioverter defibrillator. Issue 2 (29th November 2017) - Sehatbakhsh, Samineh; Kushnir, Alexander; Kabach, Mohamad; Kolek, Matthew; Chait, Robert; Ghumman, Waqas
Abstract: Implantable cardioverter defibrillators (ICDs) have been shown to have a significant benefit in reducing sudden cardiac death (SCD) in patients with systolic heart failure. Additionally, cardiac devices as a bridge to transplant or destination therapy are often used in patients with end‐stage systolic heart failure. As a result, most patients with left ventricular assist devices (LVADs) also have an ICD. Here, we present an electromagnetic interference (EMI) between HeartMate 3 LVAD and ICD. This issue might be critical for both electrophysiologists and advanced heart failure cardiologists to understand prior to implantation of ICD/LVADs in these patients.